1995
DOI: 10.3109/13813459508998138
|View full text |Cite
|
Sign up to set email alerts
|

Exercice Physique et Squelette

Abstract: The skeleton provides more than only a framework for the body. Bone is a calcified conjunctive tissue sensitive to various mechanical stimuli, mainly to those resulting from gravity and muscular contractions. Numerous animal and human studies demonstrate the importance of weight-bearing physical activity as well as mechanical loading for maintaining skeletal integrity. Lack of weight-bearing activity is dangerous for the skeleton: a decrease in bone mineral density (BMD) has been demonstrated in animals and hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 152 publications
0
5
0
Order By: Relevance
“…Mechanical loading plays a major role in the development and maintenance of bone mass. Clinical and experimental studies demonstrate that moderate and repeated physical activity is able to increase bone mass in both animals and humans (1). Mechanical loading influences bone mass through the strains it engenders into bone tissue either as a result from the strain itself or due to changes in the streaming potentials, intralacunar pressure, and fluid flow, or through deformations in the extracellular matrix (17).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical loading plays a major role in the development and maintenance of bone mass. Clinical and experimental studies demonstrate that moderate and repeated physical activity is able to increase bone mass in both animals and humans (1). Mechanical loading influences bone mass through the strains it engenders into bone tissue either as a result from the strain itself or due to changes in the streaming potentials, intralacunar pressure, and fluid flow, or through deformations in the extracellular matrix (17).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, numerous investigations have demonstrated a positive association between moderate physical activity and bone mass in humans (Barlet et al 1995). Similarly, endurance running (Saville and White 1969;Shimegi et al 1990;Forwood and Parker 1991;Yeh et al 1993), wheel running (Leblance et al 1983Newhall et al 1991;Umemura et al 1992) and jump training (Umemura et al 1995) has been shown to increase bone mass in rats.…”
Section: Introductionmentioning
confidence: 97%
“…We have previously demonstrated that treadmill running starting immediately after orchidectomy prevents bone loss in young rats, mainly by inhibiting bone resorption, as indicated by decreased urinary deoxypyridinoline (DPD) excretion (Horcajada et al 1997). It has also been demonstrated that moderate physical exercise is eective in preventing human involutional bone loss and osteoporosis (Barlet et al 1995). However it is dicult to conduct life-time studies in humans.…”
Section: Introductionmentioning
confidence: 98%
“…Regular exercise is quite an effective tool in the prevention and rehabilitation of cardiovascular diseases 13) . Barlet et al found that a regular program of weight-bearing exercise, such as walking can increase bone health and strength even among individuals with osteoporosis 14) .…”
Section: Discussionmentioning
confidence: 99%